The narrative identity dimension in transnational migrations: the Brazilian case in Santiago, Chile - Ariany da Silva Villar; Dariela Sharim (Estudios Fronterizos)
This study analyzes the narrative identity dimension related to transnational migration through the case of Brazilian migrants in Santiago, Chile. Using a phenomenological-hermeneutic research approach, we collected life stories, conducted in-depth interviews and utilized photovoice with Brazilians who have been living in the Chilean capital for at least one year. The data were collected in 2018 and 2019 and were analyzed using thematic content analysis with the help of MaxQDA 2020 software. Our findings reveal that the recognition and welcome of “Brazilianness” in Chile provide these migrants with a distinct advantage over other migrants in the receiving society in the labor, social, and interpersonal spheres. This condition, paired with everyday transnational experiences, contributed to constructing an expanded narrative of self for the participants. We interpret that this subjective expansion has configured as an interstitial space that favors the emergence of culturally hybrid narrative identities that challenge the centrality of national identities in personal narratives.